Viver além da margem: existências e resistências de mulheres criminalizadas (Ceará, 1970-1990) - Corvello, Cynthia (2022)
This dissertation seeks to: analyze the processes of criminalization and pathologization that permeated women in conflict with the law during the decades from 1970 to 1990; problematize the models of femininity of the period and the punishments directed to those who opposed these models; reflect on the relations of negotiation, insurgence or submission experienced by impoverished women, the pathologization of their violent acts and the production – the thin force – of domestic and subordinates bodies. The historical documents used for this reflection are government publications, laws, periodicals and, mainly, the prison records of the first inmates of the Female Penal Institute Desembargadora Auri Moura Costa, inaugurated in August 1974 in Fortaleza, capital of Ceará. The time frame of this research privileges the temporality of the historical documents present in the prison collection of the first group of women in custody in the institution, documents produced between the 1970s and 1990s. It is understood that during this period there was an hardening of public security policies in the context of the Civil-Military Dictatorship and the War on Drugs. That said, the inauguration of the women's prison unit in the Ceará’s State is treated in this research as an event that signaled new disciplinary strategies aligned with the management of the dictatorial government. It is understood that part of these strategies were directed to the modernization and expansion of control devices and surveillance and the insertion of punitive mechanisms based on discourses produced by criminological knowledge that constructed, in the person in conflict with the law, the subject to be transformed and the object to be studied. Among these knowledges, Psychiatry acted in a significant way in the weaving with Law and Anthropology, reinforcing gender places and functions, and in the production of the abnormal and the pathological, regarding female violence. That said, the objective of this dissertation is to historicize, from an intersectional and gender perspective, the experiences and power relations lived by criminalized women having as a motto the discourses that sought, through effects of truth, to build new subjects and subjectivities; to understand the submissions, negotiations, accommodations or insurgencies experienced by these subjects in society inside and outside the walls and to reflect on the historicity of knowledge and institutions from traces of the exercises of power between these individuals and the institutions producers/holders of knowledge.